Association of Parental Health Literacy with Treatment Adherence and Clinical Outcomes in Adolescents with Allergic Rhinitis: A Controlled Longitudinal Study - Fatih Kaplan; Abdulgani Gülyüz; Bilge Kurnaz Kaplan (Journal of Clinical Medicine, 2026)
Background: Parental health literacy may be associated with treatment adherence and clinical outcomes in adolescents with allergic rhinitis (AR), but evidence regarding these relationships remains limited. Objective: To evaluate the associations of parental health literacy with treatment adherence and clinical outcomes in adolescents with AR and to compare parental health literacy and baseline sleep-related symptom burden between adolescents with AR and healthy controls. Methods: In this controlled longitudinal observational study, 132 adolescents with AR and 120 healthy controls were enrolled. Parental health literacy was assessed using the Turkish Health Literacy Scale-32 (TSOY-32). Adolescents with AR were evaluated at baseline (T0), week 4 (T1), and week 8 (T2). Nasal symptoms were assessed using the Total Nasal Symptom Score (TNSS) and Visual Analog Scale (VAS), and sleep-related symptoms using the Pediatric Sleep Questionnaire (PSQ). Treatment adherence was classified at T2 as a single binary measure covering the entire 8-week follow-up period. Multivariable linear regression and Firth penalized logistic regression analyses were performed. Results: Adolescents with AR had significantly higher PSQ total and subscale scores and a greater prevalence of PSQ-defined high risk than healthy controls (all p < 0.001). During follow-up, PSQ, TNSS, and VAS scores decreased significantly (all p < 0.001), with greater improvements among treatment-adherent adolescents. Parental health literacy was associated with treatment adherence (p < 0.001) and with improvements in TNSS and VAS. However, after adjustment, treatment adherence—but not parental health literacy—remained independently associated with T2 PSQ, TNSS, and VAS scores. The multivariable adherence model showed high apparent discrimination within the study sample (AUC = 0.969). Conclusions: Higher treatment adherence was consistently associated with more favorable clinical outcomes in adolescents with AR. Parental health literacy was associated with treatment adherence but was not independently associated with T2 clinical outcomes after multivariable adjustment. Whether treatment adherence represents a pathway linking parental health literacy to clinical outcomes cannot be determined from the present observational study.